Tunneling in rock by drilling and blasting : workshop hosted by Fragblast 10 : the 10th International Symposium on Rock Fragmentation by Blasting, New Delhi, India, 24-25 November, 2012 - Spathis, A. T.; Gupta, R. N. 1942- (CRC Press, 2013)
Tunnelling in Rock by Drilling and Blasting presents the latest developments in the excavation of tunnels using the drilling and blasting method. Examples of work conducted throughout the world including the Indian sub-continent, Australia, and Sweden amongst others are discussed. These tunnel projects serve to illustrate the challenges and importance of drilling accuracy, the effect of geology, methods of vibration prediction and control, and techniques for assessing tunnel performance in terms of overbreak and underbreak, advance and rock mass damage. A number of case st.